Elementos Terras-Raras e Gadolínio Antropogênico na Costa Equatorial Brasileira - Costa, Antonia Rute Bezerra da (2022)
Rare Earth Elements (REE) are a group of elements with very close physical-chemical characteristics and used as efficient tracers of geochemical processes in various environments such as rivers and estuaries. Gadolinium (Gd), one of the REE, can enter the aquatic environment from anthropogenic sources such as contrast agents used in magnetic resonance and allows to trace the presence of sewage. The objectives of this study were: 1) to characterize the behavior of REE in the coastal zone of Fortaleza and in the Parnaíba River Delta and, in this way, to obtain information on the influence of these regions on the fluvial flow of these elements to the ocean and 2) to assess whether sewage is traceable in these regions. Positive anomalies of Gd were observed in the area of the submarine outfall and in two estuaries of Fortaleza, indicating that the city is a significant source of this contaminant to the ocean. The Parnaíba River Delta, in turn, did not present positive Gd anomalies, which indicates that this is a region not yet contaminated by sewage.